HUBUNGAN TINGKAT STRES DENGAN KINERJA PERAWAT DI POLIKLINIK RUMAH SAKIT Dr. OEN SOLO BARU - Yulianti, Tunjung Sri; Dewi, Devina Setya (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background this study was in the lives of everyday people cannot escape from stress, such as when humans meet challenges, threat or when it should be trying to cope with the expectations of their environment. For those who are not ready would cause a gap between body and soul. Nurses are the health care personnel who are 24 hours near the patient. the workload incurred by nurses is quite high because nursing is a profession with a group of the most front and nearest to the suffering, pain, and misery experienced by the patient and his family. Nurse at the Polyclinic Dr. Oen Solo Baru hospital Recently had a flurry of work are high, many of the demands of the work to be completed, and are expected to serve the patient with the best possible. Stressful conditions in conjunction with the nurse performance had the meaning that is important, because with a high level of stressor then it will affect the process of nursing services to patients.The purpose of this research is to know the stress level of relationship with the nurse performance at the Polyclinic Dr. Oen Solo Baru hospital.The method of this research is correlation research of two variables, by involving the first variable is the stress of work and the second variable is the performance of nurses, with statistical test Fisher with p value 0.05.The results from this study is there is no relationship between the level of stress with the nurse performance at the Polyclinic Dr. Oen Solo Baru hospital with the value of significancy 1,000 for 2-sided and 0.455 for 1-sided.Conclusion of this research is that there is no relationship between the level of stress with the nurse performance at the Polyclinic Dr. Oen Solo Baru hospital.Key words: Stress Levels, Performance.